(3TQM JYdje GdeJYde WQjb GdJYde ddRQfhLjs - (3GdYKeGfj, GHf ESeGYjd, Rjf GdYQH, EHQGgje Hf ESeGYjd eMj GdOjf, cGf MjG (B996(3g`s
(3ChdgG (B:s
(3GdMeO ddg GdPj CfYe YdjfG HCfhGY GdfYe hHYO adeG QCjJ GdcJGH GdeSei HJYdje GdeJYde eQZhHG ebHhdG CQOJ Cf CTQMg TQMG jHjf eYGbOgs
(3BNQgG (B:s
(3aCLGH Hbhdg jLOg ef jWdHg hgh cJGH eTghQ heYJHQ Hjf GdYdeGA adG HO ddWGdH ef Cf jLOg HGdBKGQ hGdCNHGQ GdePchQI ajgs
(3GdJhKjbGJ GdeQLYjI (B:s
(3cTa GdXfhf(B: 1 / 425s
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdbWQjIs
(3ehGUaGJ GdhYGA (B:s
(3Qbej edhfs
Keywords: (3GdJUha hGdBOGH GdTQYjIs